Vietnamese Catholics in the United States and Americanization: A Sociological and Religious Perspective - Phan, Peter C. (Buddhist Christian studies, 2023)
Taking a cue from Carilyn Chen's book about the Americanization of Taiwanese immigrant Buddhists, Getting Saved in America: Taiwanese Immigration and Religious Experience (2009), this essay narrates the process by which Vietnamese Catholics are "Americanized." Compared with the Taiwanese Buddhists, Vietnamese Catholics had the advantage of being members of a global Church, were from the beginning incorporated into the American Catholic Church, thereby enjoying the many benefits that this institutional incorporation brought with it, and were cared for pastorally by their own clergy. On the other hand, because of their obligation to strict adherence to the legal structures of the Catholic Church, Vietnamese American Catholics were not free to innovate institutionally as they saw fit, as were their Buddhist counterparts. The essay ends with observations on the Americanization of Vietnamese American Buddhists.